PEM electrolytic water membrane electrode and preparation method thereof
By adding high conductive electrical and high -intact second anode catalysts in the PEM electrolyte electrode, the problem of not close connection between the membrane electrode layer and poor conductivity of the catalytic layer have been solved, and the interface contact resistance and improvement are achieved. The effect of water transmission efficiency has improved the service life of membrane electrode performance and electrolytic grooves.
Patent Information
- Application Number
- CN202411775423.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-01-28
AI Technical Summary
Among the existing PEM electrolytic membrane electrodes, the connection between the membrane electrode layers is not tight, and the catalytic layer has poor electrical conductivity and mass transfer ability, resulting in large contact resistance and low water and gas transmission efficiency, which affects the performance and stability of the electrolytic cell.
In the traditional anode catalytic layer and anode multi -porous transmission layer, a new layer of second anode catalyst with high electrical and high -end hydrophilicity is added. It is prepared by electrostatic spinning technology to adjust the pore structure of the material to make it closely connected. Reduce interface contact resistance and improve water transmission efficiency.
By increasing the second anode catalytic layer, the tightness of the connection between the membrane electrode layer is improved, the interface contact resistance is reduced, the water transmission efficiency is improved, the membrane electrode performance is improved, the operating voltage of the electrolytic slot is reduced, and the service life is extended.
Smart Images

Figure CN119372686A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fuel cells, and in particular to a PEM water electrolysis membrane electrode and a preparation method thereof. Background Art
[0002] PEM (proton exchange membrane) water electrolysis technology is an important way to produce green hydrogen. Its advantages include high working current density, high hydrogen purity, fast response speed, and the ability to adapt to the volatility of renewable energy generation. Therefore, it is considered to be one of the most promising ways to produce hydrogen. The core component of the PEM water electrolyzer is the membrane electrode (MEA), which is usually composed of an anode catalyst layer, a proton exchange membrane, and a cathode catalyst layer. Sometimes, some functional layers are also included, such as a hydrogen removal layer and an ionomer transition layer. The catalytic layer of the membrane electrode is the core part of the electrochemical reaction that occurs during the electrolysis of water. The anode catalyst layer undergoes an oxygen evolution reaction, and the cathode catalyst layer undergoes a hydrogen evolution reaction. A certain voltage (usually about 2.0V) is applied between the two electrodes of the electrolyzer to drive the reaction.
[0003] As an electrochemical device, the energy efficiency and durability of the PEM water electrolyzer are closely related to its internal resistance. Lower internal resistance can not only reduce the operating voltage of the electrolyzer and reduce energy consumption, but also reduce material corrosion caused by high voltage. Therefore, the interface connection between the membrane electrode layers is required to be as tight as possible to reduce contact resistance. Traditional PEM electrolyzers usually use sintered titanium plates, titanium felt and other materials as porous transport layers. These materials play an important role in the electrolysis process. However, the interface connection between the existing porous transport layer materials and the catalytic layer is not ideal, which is mainly limited by the conductivity of the material, the surface oxide layer and the material structure.
[0004] First, the electrical conductivity of metallic titanium is relatively poor, and an oxide layer is easily formed on the surface, further reducing its electrical conductivity. Secondly, the pore structure between the porous transport layer and the catalytic layer of titanium is quite different. Taking titanium felt as an example, its pore size is usually several hundred microns, while the pores of the catalytic layer are only a few microns. The pore scales between the two differ by two orders of magnitude, which leads to loose interface contact between the membrane electrode layers, insufficient electron conduction paths, and large contact resistance. In addition, the catalyst layer of the electrolyzer often has problems such as small pore size, low porosity, and poor hydrophilicity, which makes it difficult for water vapor to be smoothly transmitted during the reaction, resulting in large transfer polarization voltage losses.
[0005] Therefore, the existing technology has the problem of loose connection between membrane electrode layers, poor conductivity and mass transfer capacity of the catalyst layer, which significantly affects the performance and stability of the PEM electrolyzer. Therefore, developing a new membrane electrode design to enhance the connection between membrane electrode layers, reduce interface contact resistance, and improve water-gas transmission efficiency has become the key to improving the performance of PEM water electrolysis technology and extending its service life. Summary of the invention
[0006] Based on this, it is necessary to provide a PEM water electrolysis membrane electrode and a preparation method thereof that can enhance the connection between membrane electrode layers, reduce interface contact resistance, and improve water gas transmission efficiency.
[0007] To achieve the above object, the present invention provides a technical solution: A PEM water electrolysis membrane electrode, characterized in that the PEM water electrolysis membrane electrode comprises, from top to bottom, an anode porous transport layer, an anode catalyst layer, a proton exchange membrane, a cathode catalyst layer, and a cathode porous transport layer; Wherein, the anode catalyst layer comprises a first anode catalyst layer and a second anode catalyst layer, and the second anode catalyst layer is located between the anode porous transport layer and the first anode catalyst layer; The second anode catalyst layer is prepared by electrospinning an oxygen evolution catalyst, a PFSA dispersion and a conductive polymer, wherein the oxygen evolution catalyst comprises at least one of iridium black, iridium oxide, iridium-based supported catalyst and alloy catalyst.
[0008] Furthermore, the conductive polymer includes at least one of polythiophene, polypyrrole and polyacetylene.
[0009] Furthermore, the pore size of the anode porous transport layer is 100 μm to 1000 μm, the pore size of the first anode catalyst layer is 0.1 μm to 10 μm, and the pore size of the second anode catalyst layer is 50 μm to 200 μm.
[0010] Furthermore, the thickness of the second anode catalyst layer is 5 μm to 20 μm.
[0011] Furthermore, the weight ratio of the PFSA dispersion to the conductive polymer is 3:1 to 1:3.
[0012] The present invention also provides a method for preparing a PEM water electrolysis membrane electrode, which is characterized by comprising the steps of: The anode porous transport layer, the second anode catalyst layer, the first anode catalyst layer, the proton exchange membrane, the cathode catalyst layer, and the cathode porous transport layer are sequentially stacked together by transfer printing to obtain the PEM water electrolysis membrane electrode.
[0013] The specific preparation steps of PEM water electrolysis membrane electrode are as follows: S100, preparing the first anode catalyst layer Alcohol and deionized water are added to a perfluorosulfonic acid (PFSA) dispersion, the PFSA is preliminarily dispersed by an ultrasonic cell disruptor, and then an oxygen evolution catalyst is added, transferred to a ball milling jar filled with ball milling beads, sealed, and dispersed again by a ball mill to obtain a first anode catalyst slurry. The oxygen evolution catalyst includes at least one of iridium black, iridium oxide, iridium-based supported type and alloy type catalyst.
[0014] Among them, the solid content of the anode catalyst slurry is 15~30%, the alcohol content is 25%~75%, the ultrasonic power is 100~500W, the material-ball ratio is 1:1~1:4, the speed is 50~500rpm, the temperature is -5~60℃, and the time is 8~72h; The first anode catalyst slurry is evenly coated on the surface of the base membrane using a desktop coater, and heated and dried to obtain a first anode catalyst layer.
[0015] The bottom plate temperature of the coating machine is 25~80℃, the coating wet film thickness is 50~150μm, the coating rod line speed is 0.1~0.5m / min, the drying time is 1~20min, the first anode catalyst layer thickness is 5~15μm, and the iridium loading is 0.3~2.0 mg / cm 2 ; S200, preparation of cathode catalyst layer Alcohol and deionized water are added to the PFSA dispersion, the PFSA is preliminarily dispersed by an ultrasonic cell disruptor, and then a hydrogen evolution catalyst is added, transferred to a ball mill jar filled with ball mill beads, sealed, and dispersed again by a ball mill to obtain a cathode catalyst slurry. The hydrogen evolution catalyst includes at least one of platinum black, platinum carbon, a platinum-based supported catalyst, and a platinum-based alloy catalyst.
[0016] Among them, the solid content of the cathode catalyst slurry is 7~13%, the alcohol content is 25%~75%, the ultrasonic power is 100~500W, the material-ball ratio is 1:1~1:4, the speed is 50~500rpm, the temperature is -5~60℃, and the time is 8~72h; Use a desktop coating machine to evenly coat the cathode catalyst slurry on the surface of the base film, heat and dry it to obtain the cathode catalyst layer. The coating machine bottom plate temperature is 25~80℃, the coating wet film thickness is 50~150μm, the coating rod line speed is 0.1~0.5m / min, the drying time is 1~20min, the cathode catalyst layer thickness is 5~15μm, and the platinum loading is 0.1~0.4 mg / cm 2 ; S300, preparing the second anode catalyst layer The oxygen evolution catalyst, PFSA dispersion and conductive polymer solution are mixed and uniformly stirred by ultrasonic stirring to form a precursor solution; the oxygen evolution catalyst comprises at least one of iridium black, iridium oxide, iridium-based supported type and alloy type catalyst. The oxygen evolution catalysts in the first anode catalyst layer and the second anode catalyst layer can be the same or different.
[0017] The precursor solution is sucked into a syringe, the syringe is connected to a propeller, the spinning nozzle is fixed on the propeller, a base film is covered on the spinning collector, and the parameters are adjusted for electrostatic spinning. After completion, it is placed in an oven and dried to obtain a second anode catalyst layer.
[0018] Among them, the voltage of electrospinning is 1KV ~30KV, the temperature of electrospinning is 20℃~80℃, the humidity of electrospinning is 20%~80%, and the time of electrospinning is 0.5h ~12h.
[0019] The pushing speed of the propeller is 0.3ml / h ~3ml / h, and the distance between the collector and the needle of the syringe is 5cm ~25cm.
[0020] S400, Preparation of PEM water electrolysis membrane electrode The first anode catalyst layer, the proton exchange membrane and the cathode catalyst layer are cut into suitable sizes and stacked together. The first anode catalyst layer and the cathode catalyst layer are transferred to both sides of the proton exchange membrane through a transfer machine to obtain a first membrane electrode. The transfer temperature of the transfer machine is 80°C ~ 180°C, the transfer pressure is 2MPa ~ 5MPa, and the transfer time is 2min ~ 10min.
[0021] The second anode catalyst layer is cut into a suitable size, and stacked on the surface of the first anode catalyst layer of the first membrane electrode prepared above. The second anode catalyst layer is transferred to the surface of the first anode catalyst layer by a transfer machine to obtain a second membrane electrode. The transfer temperature of the transfer machine is 80~180℃, the transfer pressure is 2~5MPa, and the transfer time is 2~10min.
[0022] The anode porous transport layer and the cathode porous transport layer are cut into suitable sizes, and are respectively stacked on the surfaces of the second anode catalyst layer and the cathode catalyst layer on both sides of the second membrane electrode prepared above. Under normal temperature conditions, they are pressed together by a press at a pressure of 0.5~1.5MPa to obtain a PEM water electrolysis membrane electrode.
[0023] More specifically, the proton exchange membrane is a homogeneous membrane or an enhanced membrane. Specifically, the homogeneous membrane includes at least one of Chemours' N115 and N117, and the enhanced membrane includes at least one of Hydrogen Energy's BriPEM-801, Fumatech's FS-990-PK, and Gore's M275.80. The transfer temperature is 80~180°C, the pressure is 2~5MPa, and the time is 2~10min.
[0024] The anode porous transport layer is at least one of titanium felt, sintered titanium plate and porous titanium plate; The cathode porous transport layer is at least one of titanium felt, sintered titanium plate, porous titanium plate, carbon paper and carbon cloth.
[0025] The PFSA dispersion used in the above steps can be Nafion D520 and D2020 from Chemours in the United States, or D72-25BS, D79-25BS, D87-25BS and D98-25BS from Solvay in Belgium, or IC154 and IC100 from AGC in Japan, or DHx120, DHx220 and DHx320 from Dongyue Future Hydrogen Energy in Shandong Province, PFSA dispersions of different branch lengths produced by different manufacturers, the alcohol is at least one of methanol, ethanol, n-propanol, isopropanol, ethylene glycol, n-butanol, isobutanol and sec-butanol, the ball milling beads are at least one of alumina balls, zirconia balls and agate balls, and the base film is at least one of PI, PTFE, PPS and PET.
[0026] Beneficial effects of the present invention: The present invention adds a second anode catalyst layer with high conductivity and high hydrophilicity between the traditional anode catalyst layer and the anode porous transport layer, transitions the scale difference of the two layers of materials, makes the two layers tightly connected together, reduces the interface contact resistance, improves the water vapor transmission efficiency, improves the membrane electrode performance, reduces the working voltage of the electrolyzer, alleviates high potential corrosion, and extends the service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a schematic diagram of the PEM water electrolysis membrane electrode structure; Figure 2 The scanning electron microscope morphology of common catalyst layer and titanium felt; Figure 3 This is a scanning electron microscope morphology image of the second anode catalyst layer prepared in Example 1; Figure 4 is an iV curve diagram of the embodiments and comparative examples based on BriPEM-802 membrane; Figure 5 is an iV curve diagram of an embodiment and a comparative example based on N115 film; Figure 6 The internal resistance diagram of the embodiment and the comparative example based on the BriPEM-802 membrane; Figure 7 The internal resistance diagram of the embodiment and the comparative example based on the N115 film; Figure 8 It is a voltage stability diagram of the embodiment and the comparative example under constant current density working conditions; Fig. 9 Graph showing the contact angles of Example 1 and Comparative Example 1.
[0028] Among them, 1. anode porous transport layer; 2. second anode catalyst layer; 3. first anode catalyst layer; 4. proton exchange membrane; 5. cathode catalyst layer; 6. cathode porous transport layer. DETAILED DESCRIPTION
[0029] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0030] In the examples, the test methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0031] Example 1
[0032] S100, preparing the first anode catalyst layer n-Propanol and deionized water were added to the PFSA dispersion (D79-25BS), and it was preliminarily dispersed by an ultrasonic cell disruptor. Then, an iridium oxide catalyst (TEC77110, Tanaka Precious Metals) was added, and the mixture was transferred to a ball mill filled with zirconium oxide ball milling beads and sealed. It was dispersed again by a ball mill to obtain the first anode catalyst slurry.
[0033] Among them, the solid content of the anode catalyst slurry is 25%, the alcohol content is 50%, the ultrasonic power is 300W, the material-ball ratio is 1:1, the speed is 400rpm, the temperature is 25℃, and the time is 24h; The first anode catalyst slurry is evenly coated on the surface of the PTFE membrane using a desktop coater, and heated and dried to obtain a first anode catalyst layer.
[0034] The coating machine bottom plate temperature is 50°C, the coating wet film thickness is 120 μm, the coating rod line speed is 0.2 m / min, the drying time is 5 min, the first anode catalyst layer thickness is 8 μm, and the iridium loading is 1.0 mg / cm 2 ; S200, preparation of cathode catalyst layer n-Propanol and deionized water were added to the PFSA dispersion (D79-25BS), and it was preliminarily dispersed by an ultrasonic cell disruptor, and then a platinum carbon catalyst (TEC10F50E-HT, Tanaka Precious Metals) was added, and the mixture was transferred to a ball mill filled with zirconia ball milling beads, sealed, and dispersed again by a ball mill.
[0035] Among them, the cathode catalyst slurry has a solid content of 10%, an alcohol content of 50%, an ultrasonic power of 300W, a material-to-ball ratio of 1:1, a rotation speed of 200rpm, a temperature of 25°C, and a time of 48h; The cathode catalyst slurry is evenly coated on the surface of the PTFE membrane using a desktop coater, and then heated and dried to obtain a cathode catalyst layer.
[0036] The bottom plate temperature of the coating machine was 50 °C, the thickness of the wet film was 100 μm, the coating rod line speed was 0.2 m / min, the drying time was 5 min, the cathode catalyst layer thickness was 10 μm, and the platinum loading was 0.3 mg / cm2 ; S300, preparing the second anode catalyst layer Take out iridium oxide catalyst (TEC77110), PFSA dispersion (D79-25BS) and conductive polymer solution (PEDOT:PPS) and mix them. After ultrasonic stirring, form a precursor solution. Then, suck the spinning precursor solution into the syringe, select a suitable spinning nozzle, and fix it on the propeller. Cover the spinning collector with a layer of base film and keep a suitable distance from the nozzle. Adjust the voltage, push speed, collector and needle distance, temperature and humidity parameters for electrospinning. After completion, put it in the oven and dry it to obtain the second anode catalyst layer. The weight ratio of PFSA and conductive polymer is 1:1, the voltage is 5KV, the push speed is 0.5ml / h, the distance between the collector and the needle is 10cm, the temperature is 60℃, the humidity is 45%, the collection time is 5h, and the thickness of the second anode catalyst layer is 10μm.
[0037] S400, Preparation of PEM water electrolysis membrane electrode The first anode catalyst layer, proton exchange membrane (BriPEM-802) and cathode catalyst layer were cut into appropriate sizes and stacked together. The first anode catalyst layer and the cathode catalyst layer were transferred to both sides of the proton exchange membrane by a transfer machine at 160°C and 3MPa for 5 minutes to obtain the first membrane electrode.
[0038] Transfer the second anode catalyst layer. Cut the second anode catalyst layer into a suitable size and stack it on the surface of the first anode catalyst layer of the first membrane electrode prepared above. Use a transfer machine to transfer the second anode catalyst layer to the surface of the first anode catalyst layer at 160°C and 3MPa for 5 minutes to obtain a second membrane electrode.
[0039] The anode porous transport layer and the cathode porous transport layer are cut into appropriate sizes, and are respectively stacked on the surfaces of the second anode catalyst layer and the cathode catalyst layer on both sides of the second membrane electrode prepared above. Under room temperature conditions, they are pressed together by a press at a pressure of 0.5 MPa to obtain a PEM water electrolysis membrane electrode.
[0040] Example 2
[0041] The other steps of Example 2 are the same as those of Example 1, except that: The enhanced proton exchange membrane (BriPEM-802) with a thickness of 80 μm was replaced by a homogeneous proton exchange membrane (N115) with a thickness of 127 μm.
[0042] Example 3
[0043] The other steps of Example 2 are the same as those of Example 1, except that: The short-chain branched PFSA dispersion D79-25BS was replaced with the long-chain branched PFSA dispersion (D2020).
[0044] Example 4
[0045] The other steps of Example 2 are the same as those of Example 1, except that: The anodic iridium oxide catalyst (TEC77110) was replaced with an iridium ruthenium catalyst (H2EL-30IrRu, Heraeus).
[0046] Comparative Example 1 The other steps of Example 2 are the same as those of Example 1, except that: Excluding step S300 of preparing the second anode catalyst layer, when preparing the PEM water electrolysis membrane electrode in step S400, the steps are as follows: The first anode catalyst layer, proton exchange membrane (BriPEM-802) and cathode catalyst layer were cut into appropriate sizes and stacked together. The anode catalyst layer and the cathode catalyst layer were transferred to both sides of the proton exchange membrane by a transfer machine at 160°C and 3MPa for 5 minutes to obtain the first membrane electrode.
[0047] The anode porous transport layer and the cathode porous transport layer are cut into appropriate sizes and stacked on the surfaces of the second anode catalyst layer and the cathode catalyst layer on both sides of the first membrane electrode prepared above, respectively. Under room temperature conditions, they are pressed together by a press at a pressure of 0.5 MPa to obtain a PEM water electrolysis membrane electrode.
[0048] Comparative Example 2: The other steps of Example 2 are the same as those of Example 1, except that: Excluding step S100 of preparing the first anode catalyst layer, when preparing the PEM water electrolysis membrane electrode in step S400, the steps are as follows: The second anode catalyst layer, proton exchange membrane (BriPEM-802) and cathode catalyst layer were cut into appropriate sizes and stacked together. The anode catalyst layer and the cathode catalyst layer were transferred to both sides of the proton exchange membrane using a transfer machine at 160°C and 3MPa for 5 minutes.
[0049] The anode porous transport layer and the cathode porous transport layer are cut into suitable sizes, and are respectively stacked on the surface of the second anode catalyst layer and the cathode catalyst layer of the electrode prepared above. Under room temperature conditions, they are pressed together by a press at a pressure of 0.5 MPa to obtain a PEM water electrolysis membrane electrode.
[0050] Comparative Example 3: The other steps of Example 2 are the same as those of Comparative Example 1, except that: The enhanced proton exchange membrane BriPEM-802 with a thickness of 80 μm was replaced by the homogeneous proton exchange membrane N115 with a thickness of 127 μm.
[0051] Comparative Example 4: The other steps of Example 2 are the same as those of Comparative Example 2, except that: The enhanced proton exchange membrane BriPEM-802 with a thickness of 80 μm was replaced by the homogeneous proton exchange membrane N115 with a thickness of 127 μm.
[0052] like Figure 1 As shown, compared with the existing process, the present invention adds a second anode catalyst layer 2 with high conductivity and high hydrophilicity between the traditional first anode catalyst layer 3 and the anode porous transport layer 1, transitions the scale difference of the two layers of materials, makes the two layers tightly connected together, reduces the interface contact resistance, improves the water vapor transmission efficiency, improves the membrane electrode performance, reduces the working voltage of the electrolyzer, alleviates high potential corrosion, and extends the service life.
[0053] Figure 2 This is a scanning electron microscope morphology of a common catalytic layer and titanium felt.
[0054] like Figure 2 As shown, the pore structures between the common titanium porous transport layer (titanium felt) and the catalytic layer are quite different. The pore size of the titanium felt is 100μm~1000μm, while the pore size of the catalytic layer is 0.1μm~10μm. The pore scales between the two differ by two orders of magnitude, which leads to loose interface contact between the membrane electrode layers, insufficient electron conduction path, and large contact resistance.
[0055] Figure 3 This is a scanning electron microscope morphology of the second anode catalyst layer prepared in Example 1. Figure 3 As shown, the pore size of the second anode catalyst layer prepared in Example 1 is 50μm~200μm, and the pore size of the second anode catalyst layer is between the anode porous transport layer and the catalyst layer, which can effectively alleviate the high interface contact resistance caused by the large scale span, and the porous structure has excellent hydrophilicity.
[0056] The membrane electrodes prepared in the examples and comparative examples were characterized, including single cell test, internal resistance and constant current density life test, and contact angle test.
[0057] 1. Single battery test: Use 25cm 2The single electrolyzer was assembled, the cathode used a direct flow channel, the porous transport layer was 0.4mm titanium felt, the anode used a lattice flow channel, the porous transport layer was 0.4mm platinum-plated titanium felt, and the assembly pressure was 3.5MPa. The test was carried out on the electrolytic water test system, with water supply on one side of the anode, a flow rate of 200ml / min, a temperature of 60℃, and normal pressure.
[0058] The iV curve test adopts constant current mode, gradually increasing the current density measurement voltage, 0-2A / cm 2 Every 0.1A / cm 2 Take point, 2~4A / cm 2 Every 0.2A / cm 2 Take a point, after the current density changes, wait for 3 minutes until the voltage stabilizes and then record the data. The results are as follows Figure 4 and Figure 5 shown.
[0059] like Figure 4 As shown, the PEM membrane electrodes prepared in Example 1, Example 3 and Example 4 have good IV performance, and the electrolysis voltages are both comparable to those in Comparative Example 1 and Comparative Example 2.
[0060] From the image comparison of Example 1 and Example 3, it can be seen that no matter whether the membrane electrode is prepared using a short-chain PFSA dispersion or a long-chain PFSA dispersion, the second anode catalyst layer having both conductivity and hydrophilicity has the same obvious effect on improving the IV performance of the membrane electrode.
[0061] From the image comparison of Example 1 and Example 4, it can be seen that no matter whether the membrane electrode is made of iridium oxide or iridium ruthenium catalyst, the second anode catalyst layer with both conductivity and hydrophilicity has the same obvious effect on improving the IV performance of the membrane electrode.
[0062] like Figure 5 As shown, relative to the enhanced proton exchange membrane BriPEM-802 used in Example 1, Example 2 replaces the proton exchange membrane with a homogeneous proton exchange membrane N115, and the membrane electrode provided by Example 2 has good IV performance, and the electrolysis voltage is lower than that of Comparative Examples 3 and 4. It can be seen that whether an enhanced proton exchange membrane or a homogeneous proton exchange membrane is used, the second anode catalyst layer with both conductivity and hydrophilicity has the same obvious effect on improving the IV performance of the membrane electrode.
[0063] 2. Internal resistance and constant current density life test: The internal resistance test uses an electrochemical workstation and amplifier (Solartron) with a frequency range of 2000Hz~0.1Hz to test the high-frequency resistance under different current densities, which is the internal resistance of the electrolytic cell.
[0064] The constant current density life test adopts constant current mode with a current density of 3A / cm2 , record voltage change data.
[0065] like Figure 6 As shown, the membrane electrode provided by Example 1, Example 3, and Example 4 has a lower internal resistance, which is lower than that of Comparative Example 1 and Comparative Example 2, indicating that the second anode catalyst layer has a strong conductivity and can effectively reduce the internal resistance of the membrane electrode.
[0066] like Figure 7 As shown, relative to the enhanced proton exchange membrane BriPEM-802 used in Example 1, Example 2 replaces the proton exchange membrane with the homogeneous proton exchange membrane N115. The PEM membrane electrode prepared in Example 2 has a lower internal resistance, which is lower than that of Comparative Examples 3 and 4. It can be seen that no matter whether an enhanced proton exchange membrane or a homogeneous proton exchange membrane is used, the second anode catalyst layer has the same obvious effect on reducing the internal resistance of the membrane electrode.
[0067] like Figure 8 As shown, Comparative Example 1 only contains a first anode catalyst layer prepared by a coating process, while Comparative Example 2 only contains a second anode catalyst layer prepared by an electrospinning process. Relative to Comparative Example 1 and Comparative Example 2, the PEM membrane electrode prepared in Example 1, which contains both a first anode catalyst layer prepared by a coating process and a second anode catalyst layer prepared by an electrospinning process, shows lower voltage and stronger stability during the constant current density life test. The stability of Example 1 is significantly better than that of the membrane electrode prepared in Comparative Example 1 without the second anode catalyst layer and Comparative Example 2 without the first anode catalyst layer. This indicates that the second anode catalyst layer having both conductivity and hydrophilicity has a significant effect on improving the stability of the membrane electrode.
[0068] 3. Contact angle test: The contact angle test was conducted by using a contact angle tester. 2 μL of water was dropped on the surface of the samples prepared in Example 1 and Comparative Example 1. After waiting for 5 seconds, photos were taken to record the contact angles. Fig. 9 shown.
[0069] like Fig. 9 As shown, the PEM membrane electrode prepared in Example 1 has a smaller contact angle of 69°, while the contact angle of the membrane electrode prepared in Comparative Example 1 without the second anode catalyst layer is 127°. The contact angle in Comparative Example 1 is significantly larger than the contact angle in Comparative Example 1, indicating that the surface of the PEM membrane electrode prepared in Example 1 with the second anode catalyst layer added is more hydrophilic, thereby also indicating that the second anode catalyst layer can improve the water vapor transmission efficiency in the PEM membrane electrode.
[0070] It should be noted that the specific parameters or some reagents in the above embodiments are specific embodiments or preferred embodiments of the present invention, rather than limiting the present invention; those skilled in the art can make adaptive adjustments within the scope of the present invention.
Claims
1. A PEM water electrolysis membrane electrode, characterized in that: The PEM water electrolysis membrane electrode comprises, from top to bottom, an anode porous transport layer, an anode catalyst layer, a proton exchange membrane, a cathode catalyst layer, and a cathode porous transport layer; Wherein, the anode catalyst layer comprises a first anode catalyst layer and a second anode catalyst layer, and the second anode catalyst layer is located between the anode porous transport layer and the first anode catalyst layer; The second anode catalyst layer is prepared by electrospinning an oxygen evolution catalyst, a PFSA dispersion and a conductive polymer.
2. The PEM water electrolysis membrane electrode according to claim 1, characterized in that: The conductive polymer includes at least one of polythiophene, polypyrrole and polyacetylene.
3. The PEM water electrolysis membrane electrode according to claim 1, characterized in that: The pore size of the anode porous transport layer is 100 μm to 1000 μm, the pore size of the first anode catalyst layer is 0.1 μm to 10 μm, and the pore size of the second anode catalyst layer is 50 μm to 200 μm.
4. The PEM water electrolysis membrane electrode according to claim 1, characterized in that: The thickness of the second anode catalyst layer is 5 μm to 20 μm.
5. The PEM water electrolysis membrane electrode according to claim 1, characterized in that: The weight ratio of PFSA dispersion to conductive polymer is 3:1~1:
3.
6. The PEM water electrolysis membrane electrode according to claim 1, characterized in that: The preparation steps of the second anode catalyst layer include: The oxygen evolution catalyst, the PFSA dispersion and the conductive polymer solution are mixed and uniformly stirred by ultrasonication to form a precursor solution; The precursor solution is sucked into a syringe, the syringe is connected to a propeller, the spinning nozzle is fixed on the propeller, a base film is covered on the spinning collector, and the parameters are adjusted for electrostatic spinning. After completion, it is placed in an oven and dried to obtain a second anode catalyst layer.
7. The PEM water electrolysis membrane electrode according to claim 6, characterized in that: The voltage of electrospinning is 1KV ~30KV, the temperature of electrospinning is 20℃~80℃, the humidity of electrospinning is 20%~80%, and the time of electrospinning is 0.5h ~12h.
8. The PEM water electrolysis membrane electrode according to claim 6, characterized in that: The pushing speed of the propeller is 0.3ml / h~3ml / h, and the distance between the collector and the needle of the syringe is 5cm~25cm.
9. The PEM water electrolysis membrane electrode according to claim 1, characterized in that: The oxygen evolution catalyst comprises at least one of iridium black, iridium oxide, iridium-based supported catalyst and alloy catalyst.
10. A method for preparing a PEM water electrolysis membrane electrode according to any one of claims 1 to 9, characterized in that: Includes steps: The anode porous transport layer, the second anode catalyst layer, the first anode catalyst layer, the proton exchange membrane, the cathode catalyst layer, and the cathode porous transport layer are sequentially stacked together by transfer printing to obtain the PEM water electrolysis membrane electrode.